Exploring the intangible player characteristics` that junior hockey scouts consider when evaluating draft-eligible prospects - Guenter, R. W. (University of Alberta, 2018)
he overarching purpose of this study was to systematically explore and identify the `intangible player characteristics` (beyond physical, technical, and tactical abilities) that scouts consider when determining the draft-suitability of eligible `minor hockey` players in a Canadian major junior hockey league. More specifically, the study addressed three primary research questions: (1) "what are the `intangible player characteristics` that junior hockey scouts consider when evaluating draft-eligible prospects?", (2) "why are these `intangible player characteristics` deemed important in the evaluation process?", and (3) "how do junior hockey scouts gather and use intangible player characteristics in making their final decisions about the draft-suitability of draft-eligible players?" To address these questions, 16 scouts (who had a minimum of 5 years scouting experience in the league: M experience = 16.56 years, SD = 10.15), participated in semi-structured interviews. Qualitative description was used, a pragmatic and applied methodology that is intended to generate `straight` answers to questions of relevance for a specific group (Holt et al., 2018; Sandelowski, 2000, 2010). Interviews were transcribed verbatim and subjected to an inductive content analysis procedure that produced six major themes that were labelled, (a) playing ability, (b) organizational culture, (c) desirable intangibles that enhance draft status, (d) undesirable intangibles that diminish draft status, (e) the `list`, and (f) the investigative process. All scouts began their evaluation processes by observing players in competition and determining whether draft prospects had sufficient physical, technical, and tactical abilities to play in the league. Organizational culture acted as a guide for teams that determined which intangible characteristics were considered and given the most weight in the evaluation process. Within this context, scouts considered the harder to measure intangible characteristics that were deemed to either enhance or diminish the draft status of a player. Intangible characteristics that enhanced the draft status of players were captured by four primary sub-themes labelled compete, character, leadership/team player, and passion (i.e., love of the game). Intangible characteristics that diminished the draft status of players were also captured by four primary sub-themes: lack of enhancers, (poor) body language, selfish tendencies, and (poor) parental behavior. Intangible characteristics were used to develop `the list` that ranked the draft status of players; intangible characteristics were often used by teams to break ties when a number of players had similar rankings in terms of their physical, technical, and tactical abilities. Some diminishing intangibles were deemed so serious that teams decided not to draft the player at all, regardless of playing ability. Overall, participants referred to scouting as an on-going investigative process that could last an entire season where information regarding player intangibles was collected from a variety of sources. The results of the study add to the existing talent-identification literature in sport, and indicate that selection to higher levels of competitive sport in youth hockey is determined by many factors that go beyond the physical, technical, and tactical abilities of players. Applied-practice implications for scouts, hockey organizations, coaches, athletes, and athletes` parents are discussed.